Are false implicatures lies? An empirical investigation. (31st August 2018) - Weissman, Benjamin; Terkourafi, Marina
Abstract : Lies are typically defined as believed falsehoods asserted with the intention of deceiving the hearer. A particularly problematic case for this definition is that of false implicatures. These are prototypically cases where the proposition expressed by the speaker's utterance is true, yet an implicature conveyed by this proposition in context is false. However, implicature is a diverse category and whether a blanket statement such as "false implicatures are lies, " as some have argued can account for all of them is open to investigation. We present an experimental investigation of whether naïve participants define different types of implicatures as lies. Our results show that only a couple of types of implicatures were strongly rated as lies by participants. These results suggest that participants distinguish between different types of communicated meanings on linguistic grounds, contributing both to the literature on lying, as well as to theoretical discussions of how different types of meaning are communicated.